Pemilihan Layanan Menonton Film Pada Mahasiswa Fakultas Ilmu Pemerintahan dan Ilmu Politik Universitas Riau - Ayun, Nafisah Qurrota; Asriwandari, Hesti (Jurnal Ilmiah Wahana Pendidikan, 2025)
The choice of movies viewing services is a decision made by students of the Faculty of Social and Political Sciences (FISIP) at Universitas Riau in selecting between streaming services and cinema viewing, considering various factors that influence this choice. This research aims to uncover the internal and external factors influencing students in choosing film viewing services using popular culture theory. The method used is a descriptive quantitative approach, with data collected through questionnaires distributed directly and online (Google Form). The results of the study show that the majority of FISIP Universitas Riau students prefer legal streaming services, with WeTV being the most popular service. Additionally, cinemas are also a popular choice among students, with CGV Transmart Pekanbaru being the most favored cinema. The internal factor that most influences movies viewing decisions among FISIP Universitas Riau students is interest. High interest indicates that individual preferences play a significant role in determining the choice of film viewing services. Meanwhile, the most influential external factor is lifestyle. This external factor shows that film viewing choices are also influenced by social trends and how students identify themselves within their social environment.